1974
DOI: 10.1073/pnas.71.9.3492
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Major Cell Surface Glycoprotein from Fibroblasts

Abstract: A cell surface component has been isolated in partially purified form from cultured chick embryo and chick heart fibroblasts. This glycoproteiri is similar to a protein recently reported to be present at the surface of normal cells, and missing after neoplastic transformation. It is a major cell surface glycoprotein that is synthesized by cultured fibroblasts, but is not collagen. It is shown to be markedly trypsin-sensitive, and its recovery from the cell surface is dependent on cell density. It is excluded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(91 citation statements)
references
References 39 publications
(32 reference statements)
5
86
0
Order By: Relevance
“…Fibronectins are highmolecular-mass adhesive glycoproteins present in the extracellular matrix and in body fluids (Yamada and Weston, 1974), and oncofetal fibronectin is characterized by the presence of the oncofetal domain, which is absent in normal fibronectin. The oncofetal domain is recognized by a monoclonal antibody called FDC-6 (Matsuura and Hakomori, 1985), and many researchers have used this antibody to report the existence of oncofetal fibronectin in malignant tissues such as breast, colon and gastric cancers (Loridon-Rosa et al, 1990;David et al, 1993;Inufusa et al, 1995).…”
mentioning
confidence: 99%
“…Fibronectins are highmolecular-mass adhesive glycoproteins present in the extracellular matrix and in body fluids (Yamada and Weston, 1974), and oncofetal fibronectin is characterized by the presence of the oncofetal domain, which is absent in normal fibronectin. The oncofetal domain is recognized by a monoclonal antibody called FDC-6 (Matsuura and Hakomori, 1985), and many researchers have used this antibody to report the existence of oncofetal fibronectin in malignant tissues such as breast, colon and gastric cancers (Loridon-Rosa et al, 1990;David et al, 1993;Inufusa et al, 1995).…”
mentioning
confidence: 99%
“…The cell monolayers were then extracted for 2 h at 37°C with medium 199 containing 1 M urea and 0.4 mM phenyl methyl sulfonyl fluoride (11,38). The extract was removed and N-ethyl maleimide, EDTA, and pepstatin added to yield the same final concentrations as used in processing the pestculture medium.…”
Section: Antibodies and Antigens Plasma Fn And Goat And Rabbit Antibmentioning
confidence: 99%
“…Endothelial cell monolayers labeled with PH] leucine were extracted with 1 M urea for 2 h at 37°C since it has been shown that insoluble fibroblast FN can be extracted using this procedure (11,38). The urea extract was analyzed by the Protein A-Sepharose technique described above.…”
Section: Immunoisolation Of Endothelialmentioning
confidence: 99%
“…We describe here the surface-labelling patterns observed in (i) (Yamada & Weston, 1974;Keski-Oja et al, 1976;Benenson et al, 1977). The major iodinated band corresponded to a component with a mol.…”
Section: Surface-labelling Patternsmentioning
confidence: 86%